Palaeoenvironmental dynamics at the southern Alpine foothills between the Neolithic and the Bronze Age onset: a multi-proxy study from Bande di Cavriana (Mantua, Italy) - Zanon, Marco; Unkel, Ingmar; Andersen, Nils; Kirleis, Wiebke (Quaternary science reviews, 2019)
The onset of the Bronze Age (approximately 4150yrscal. BP) in the southern Lake Garda region (N-Italy) is marked by an increase in the number of settlements and by the widespread adoption of pile-dwelling building techniques. The prominence of this phenomenon polarized the attention of local palaeoenvironmental investigations. As a result, pre-Bronze age landscape and climate dynamics have been investigated to a lesser degree. In an attempt to address this disparity, our contribution focuses on the period between ∼7100 and ∼3800 yrs cal. BP, i.e. approximately between Early Neolithic and Early Bronze Age. The location of our analysis is the former lake of Bande di Cavriana (Mantua). Multi-proxy investigations highlight few major climatic shifts prior to the Bronze Age onset. A first transition into more warm/dry conditions is recorded between ∼6300 and 6100yrscal. BP. Similar conditions occur again after ∼4600yrscal. BP, peaking at ∼4300yrscal. BP. Speculatively, taking into account dating uncertainties, this second shift might represent the local expression of the ‘4.2Ka’ event. A marked transition into a colder/more humid situation occurs then after ∼4300yrscal. BP and persists into the Bronze Age. Major vegetational changes begin during the Neolithic with the steady rise of Carpinus betulus pollen (from ∼5700yrscal. BP). A more rapid expansion of this taxon after ∼5100yrscal. BP might reflect shifts in forest exploitation strategies during the Copper Age (e.g. coppicing) or changes in the ruminant fauna (e.g. grazing vs. browsing habits), arguably due to human intervention. Nonetheless, pollen grains of anthropogenic indicators appear with consistent frequency only since the Bronze Age. The establishment of the Bande di Cavriana pile dwelling (∼3950yrscal. BP) is marked by declining arboreal pollen values and growing anthropogenic taxa. This behavior likely reflects a more intense landscape exploitation (deforestation, expansion of arable fields and meadows), although an influx of herbaceous pollen from near-site activities (e.g. cereal processing, garbage dumping) should not be overlooked.
Gesehen am 19.02.2025